Removal of dye using powdered activated carbon coated on polyurethane foam - Ki, Eileen Li Sze (2023)
This study investigates the potential use of powdered activated carbon coated on polyurethane foam (PAC/PUF) as an adsorbent to remove Congo Red dye from synthetic aqueous solution. The adsorbent is crucial to the removal of Congo Red as the dye is known to be carcinogenic and mutagenic in nature. A little concentration of less than 1 part per million (ppm) is enough to pollute the water bodies, prevent photosynthesis and affect aquatic growth. The PAC/PUF was synthesized by the dip-coating method and characterized by scanning electron microscopy with energy dispersive X-ray (SEM-EDX), Xray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. The findings indicated that PAC was effectively coated on the dodecahedral skeleton surface of the PUF. Response surface methodology based on central composite design was used to optimize the effect of different adsorption parameters such as the pH, contact time, and initial concentration of dye. The optimal adsorption efficiency of Congo Red was 89.86 % at a pH of 3.854, contact time of 137.55 min, and initial concentration of dye at 33.566 mg/L. Removal of dye in low pH was better than in high pH solutions. The efficiency of adsorption improved with longer contact time but declined with increasing initial dye concentration. The kinetic studies indicated that the adsorption kinetic of Congo Red onto PAC/PUF followed the pseudo-second order kinetic model. The equilibrium data also revealed that the Langmuir isotherm model was more suitable for describing the dye adsorption. According to EDX, XRD, and FTIR characterizations, Congo Red was successfully adsorbed by PAC/PUF, suggesting both electrostatic and physical interactions between the dye and the PAC/PUF surface functional groups. Lastly, a comparison among PAC/PUF, PAC, and PUF adsorptions showed that PAC/PUF obtained the highest adsorption efficiency of Congo Red, further proved the potential use of PAC/PUF in adsorbing Congo Red.